2008
DOI: 10.1016/j.ijgo.2008.10.015
|View full text |Cite
|
Sign up to set email alerts
|

Effect of estradiol on oocyte development

Abstract: Objective To determine whether elevated serum estradiol (E2) concentrations in oocyte donors affect assisted reproduction outcome. Method In a retrospective cohort study of 58 consecutive oocyte donation cycles, donors were stratified into 2 groups according to E2 concentration, group 1 (n=32; E2≤2000 pg/mL [range 456–2000 pg/mL]) and group 2 (n=27; E2>2000 pg/mL [range, 2062–6957 pg/mL]). Data were analyzed using the t test and χ2 test. Results Donors in group 1 produced significantly less oocytes than do… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 24 publications
(49 reference statements)
1
8
0
Order By: Relevance
“…1 Our in vivo study showed that methionine supplementation increased the serum levels of E 2 and PGE 2 and decreased the serum P 4 level during estrus. Similarly, an increase in plasma estradiol has been reported to increase the number of ovulations and embryos produced, 67,68 but the increase of progesterone concentration inhibits dominant follicle development and ovulation. 69 PGE 2 promotes cumulus expansion and participates in meiosis and ovulation during oocyte development.…”
Section: Discussionmentioning
confidence: 98%
“…1 Our in vivo study showed that methionine supplementation increased the serum levels of E 2 and PGE 2 and decreased the serum P 4 level during estrus. Similarly, an increase in plasma estradiol has been reported to increase the number of ovulations and embryos produced, 67,68 but the increase of progesterone concentration inhibits dominant follicle development and ovulation. 69 PGE 2 promotes cumulus expansion and participates in meiosis and ovulation during oocyte development.…”
Section: Discussionmentioning
confidence: 98%
“…We found that the E2 levels associated with the ideal ES on day 2 were E2 16 =3.309±189pg/ml. It has been proposed that E2>5.000 pg/ml can be considered an acceptable upper limit (Wu CH et al, 2007), while others suggest that the limit of 2.000pg/ml is neither favorable nor harmful to the outcome of IVF (Bianco K et al, 2009). An optimal range of the E2 levels during a fresh IVF-ET cycle was recently proposed to be 1000 to 3148 pg/mL, with regard to the quality of oocytes retrieved, implantation rates, as well as the incidence of LBW outcomes (Li X et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…There has been controversy regarding the effect of higher estradiol levels on oocyte and embryo quality. In mice, higher estradiol levels were reported to have a direct toxic effect on embryo quality and development in vitro [47], however the detrimental effects of higher estradiol levels on embryo development in the human have not been proven [48,47]. Of interest, Balakier et al recorded significantly higher E 2 levels and a higher number of oocytes in cohorts that contained giant oocytes compared with controls [49].…”
Section: Discussionmentioning
confidence: 99%